2017
DOI: 10.3390/antibiotics6020012
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria from Animals as a Pool of Antimicrobial Resistance Genes

Abstract: Antimicrobial agents are used in both veterinary and human medicine. The intensive use of antimicrobials in animals may promote the fixation of antimicrobial resistance genes in bacteria, which may be zoonotic or capable to transfer these genes to human-adapted pathogens or to human gut microbiota via direct contact, food or the environment. This review summarizes the current knowledge of the use of antimicrobial agents in animal health and explores the role of bacteria from animals as a pool of antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
165
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(185 citation statements)
references
References 195 publications
(540 reference statements)
3
165
1
3
Order By: Relevance
“…The spread of antibiotic-resistance pathogens in the environment is a great concern in public health. Livestock species are a known reservoir of antibiotic resistance genes (ARG) [33].…”
Section: Antibiotic Resistance Genesmentioning
confidence: 99%
“…The spread of antibiotic-resistance pathogens in the environment is a great concern in public health. Livestock species are a known reservoir of antibiotic resistance genes (ARG) [33].…”
Section: Antibiotic Resistance Genesmentioning
confidence: 99%
“…In 1951, Starr and Reynolds published the first report on suspected antimicrobial resistance (AMR) in livestock farming [127]. Since then, AMR are rapidly rising due to factors like global trade and the intense international transport of animals [128]. Harbarth et al (2015) refer to the fact that the extensive use of antibiotics always stressed bacteria to develop mutations, or recombinant pieces of DNA to resist antibiotic [129].…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…From the OH-perspective, the same antibiotic is deployed in veterinary and human medicine [131]. Consequently, the transfer of resistant strains to humans can occur through food products, direct contact or contaminated environments [128]. AMR in horses was first documented in 1970 [132], almost twenty years after the first discovery in animals.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…Previous studies have shown food and the environment to contain ARG found in pathogenic bacteria (12, 23, 24). Environmental reservoirs of ARG-containing pathogens include lakes and rivers (18), wastewater treatment plants (25, 26), houseflies (27), livestock (12, 28, 29), soil and manure (29, 30), retail meat products (12, 3133), companion animals (5, 6, 8, 28, 34), alfalfa sprouts (35), retail spinach (15), and other vegetables (36).…”
Section: Introductionmentioning
confidence: 99%